Landscape of expression profiles in esophageal carcinoma by The Cancer Genome Atlas data. Issue 8 (24th September 2015) - Zhan, C.; Yan, L.; Wang, L.; Jiang, W.; Zhang, Y.; Xi, J.; Jin, Y.; Chen, L.; Shi, Y.; Lin, Z.; Wang, Q.
Summary: In this study, we explored the gene and microRNA (miRNA) expressions profile of esophageal carcinoma. The expression data for messenger RNAs and miRNAs in normal and cancerous esophageal tissues were obtained from the Cancer Genome Atlas database and then the differentially expressed genes and miRNAs were identified. As a result, we identified 2962 genes and 45 miRNAs differentially expressed in esophageal carcinoma compared with normal esophageal tissues. Subsequently, the altered gene functions and signaling pathways were investigated using gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses, and these differentially expressed genes were significantly enriched in the cell cycle, cell migration, mitogen‐activated protein kinase (MAPK) and toll‐like receptor signaling pathway, and so on. Then the regulatory relationships between the differentially expressed miRNAs and genes were examined with Targetscan and Miranda, and the potential target sites of transcription factors (TFs) in the promoter regions of these miRNAs and genes were identified using the TRANSFAC database. Finally the TF–miRNA–gene network in esophageal cancer was established, summarizing the regulatory links among the TFs, differentially expressed miRNAs and differentially expressed genes. Factors such as core promoter‐binding protein (CPBP), nuclear factor of activated T‐cells 1 (NFAT‐1), miR‐30c‐5p, were located in the central hub of this network, highlighting their vital roles in esophageal tumorigenesis. These findings may extend our understanding of the molecular mechanisms underlying esophageal carcinoma and promote new perspectives for prevention, diagnosis and treatment.